2020
DOI: 10.3390/biom10101408
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Guanylate Cyclase Activating Protein 1 (GCAP1) Dimeric Assembly by Ca2+ or Mg2+: Hints to Understand Protein Activity

Abstract: The guanylyl cyclase-activating protein 1, GCAP1, activates or inhibits retinal guanylyl cyclase (retGC) depending on cellular Ca2+ concentrations. Several point mutations of GCAP1 have been associated with impaired calcium sensitivity that eventually triggers progressive retinal degeneration. In this work, we demonstrate that the recombinant human protein presents a highly dynamic monomer-dimer equilibrium, whose dissociation constant is influenced by salt concentration and, more importantly, by protein bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 43 publications
(72 reference statements)
1
23
0
Order By: Relevance
“…Several lines of evidence in the last years have indicated that WT GCAP1 is a functional dimer under physiological conditions [ 36 , 37 ]; thus, we conducted analytical gel filtration and Dynamic Light Scattering (DLS) measurements to address the effects of the double point mutation on the quaternary structure of GCAP1, as well as on its aggregation propensity. Analytical Size exclusion Chromatography (SEC) chromatograms ( Figure 5 A) of the double mutant showed a prominent peak which shifted from 14.58 mL ( Figure 5 A, blue trace) in the presence of Mg 2+ (corresponding to a molecular mass (MM) of 38.2 kDa, Table 2 ) to 14.50 mL ( Figure 5 A, red trace) in the presence of Ca 2+ (corresponding to a MM of 40.2 kDa, Table 2 ), thus suggesting that the double mutant is predominantly a dimer upon cation binding.…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence in the last years have indicated that WT GCAP1 is a functional dimer under physiological conditions [ 36 , 37 ]; thus, we conducted analytical gel filtration and Dynamic Light Scattering (DLS) measurements to address the effects of the double point mutation on the quaternary structure of GCAP1, as well as on its aggregation propensity. Analytical Size exclusion Chromatography (SEC) chromatograms ( Figure 5 A) of the double mutant showed a prominent peak which shifted from 14.58 mL ( Figure 5 A, blue trace) in the presence of Mg 2+ (corresponding to a molecular mass (MM) of 38.2 kDa, Table 2 ) to 14.50 mL ( Figure 5 A, red trace) in the presence of Ca 2+ (corresponding to a MM of 40.2 kDa, Table 2 ), thus suggesting that the double mutant is predominantly a dimer upon cation binding.…”
Section: Resultsmentioning
confidence: 99%
“…This happens because the relatively subtle movement of the exiting helix in EF4 affects the GCAP1 fold on the other side of the molecule [ 63 ] (Fig. 3 ) and dimerization state of GCAP1 [ 12 , 64 ]. Extensive site-directed mutagenesis of GCAP2 [ 32 , 78 ] and especially GCAP1 [ 92 ] identified the cyclase binding interface of GCAP as a compact patch of the residues located on one side of the molecule and occupying large portions of EF1, -2, and a part of the entering helix of EF3 [ 92 ] (Fig.…”
Section: Metal Binding Properties Of the Photoreceptor-specific Ef-hand Sensor Proteinsmentioning
confidence: 99%
“…WT-GCAP1 forms functional dimers under physiological conditions [ 35 , 36 ]. We tested whether this was the case also for N104H-GCAP1 by running analytical gel filtration ( Figure 8 A) and DLS ( Figure 8 B) measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, we found that point mutations in the same position (Asn104) of the GUCA1A gene not only lead to clinically different phenotypes, but also generate distinct molecular phenotypes despite the absence of major structural alterations observed in any case (this study and previous ones [ 20 , 28 ]). Mutation-specific sensitivity toward cations, subtle alterations of protein stability in the presence of Mg 2+ and Ca 2+ , specific alteration of protein flexibility in distinct signaling states and the dependence of GCAP1 dimerization on the presence of specific cations [ 36 ] all point to a very complex molecular scenario, in which focusing on the effects of mutations on individual proteins might be of little use in advancing the molecular understanding of disease. Instead, unveiling the molecular details of the protein–protein and protein–ion interactions involved in the altered signaling cascade should be the final goal to achieve a molecular-level understanding of the extremely heterogenous retinal dystrophies, including COD, and would constitute a solid basis for designing effective therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%